Changes in physical performance of amateur mountain bikers in the preparatory period - Bazanska-Janas, M.; Janas, M. (Polish Journal of Sport and Tourism, 2020)
Introduction: The aim of the research was to assess the changes in the main physical performance indicators, i.e. maximum oxygen uptake (VO2max), the threshold of anaerobic changes (AT) and "exercise efficiency" (oxygen consumption/power; VO2/WR) in amateur mountain bikers in the preparatory period. In addition, diagnostic usefulness was made of selected respiratory, circulatory and metabolic parameters to assess the training progress in cycling. Materials and methods: Thirty-six men training in amateur mountain biking took part in the research. Each of them underwent three ergospirometry tests at the beginning, in the middle (after 7 weeks) and at the end of the preparatory period (after 14 weeks). The results obtained at the AT threshold and at maximum effort were analysed to check how physical training in the preparatory period affected selected exercise parameters. Results: No significant changes in the VO2max value were observed during the preparatory period, but a significant increase in this indicator (in absolute terms and in terms of body weight) was found at the AT level. An increase was noted in power as well as in measured metabolic, ventilation and circulatory parameters with the exception of heart rate and ventilation equivalent oxygen. VO2/WR decreased, which indicates an improvement in the effectiveness of the effort. Conclusions: For Polish amateur cyclists with extensive training experience, the most diagnostic indicators in the preparatory period include improving the AT threshold (shift towards higher % VO2max and higher generated power) and increasing exercise efficiency.